Corneal Biomechanics and Their Impact on Glaucoma Progression - Shahid Anwar Bhatti, Syed Noor, Mohammad Parvez, Abdul Munim, Hira Ali, Abdul Rafe, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The evolution of primary open-angle glaucoma (POAG) is examined in this work in relation to corneal biomechanics, especially corneal hysteresis (CH), corneal resistance factor (CRF), and central corneal thickness (CCT). Methodology: 116 POAG patients were included in this one-year research conducted at Department of Ophthalmology, Northwest General Hospital, Peshawar from May 2022 to April 2023. The Ocular Response Analyzer (ORA) was used to quantify corneal biomechanics, and Goldmann applanation tonometry (GAT) and dynamic contour tonometry (DCT) were used to measure intraocular pressure (IOP). Visual field tests and optic nerve evaluation were used to track the disease's development. The association between ocular parameters and the development of glaucoma was assessed using statistical tests, such as regression and correlation analysis. Results: Participants were 42% female and 58% male, with a mean age of 58.3 years (SD = 9.2). The development of glaucoma was significantly correlated negatively with both CH (r = -0.45, p < 0.01) and CRF (r = -0.42, p < 0.01). No significant link was shown by CCT (r = 0.02, p = 0.79). CH and CRF were found to be independent predictors of progression by multivariate regression (β = -0.33, p = 0.002 for CH, β = -0.31, p = 0.004 for CRF). Conclusion: corneal hysteresis and corneal resistance factor have a considerable impact on the course of glaucoma, indicating that they may be useful prognostic indicators. The effect of central corneal thickness was not the same. These results provide credence to the use of biomechanical testing in clinical settings to improve the treatment of glaucoma. Keywords: Glaucoma, Corneal Biomechanics, Corneal Hysteresis, Corneal Resistance Factor, Disease Progression